Different performance characteristics among students in Malaysia - Norjali Wazir, Mohd Rozilee Wazir; Ujang, Aris Fazil; Amri, Saidon (Universiti Putra Malaysia Press, 2017)
The main aim of this study is to examine and define performance characteristics for the male students and female students in 3 types of school in Malaysia. A sample of 1083 students (male=625, Female 458) age between 13 years to 16 years participated in this study. The students are from 3 different types of school, namely National Sport School (n=300), State Sport School (n=333) and Normal School (n=450). There were 190 male and 110 female from National Sport School, 210 male and 123 female from State Sport School. Meanwhile, there were 225 male and 225 female from the Normal School. The students from National Sport School and State Sport School consists of young athletes. Meanwhile, the students from Normal School just ordinary students with various backgrounds. Height and weight measurement is to indicate students’ anthropometry measurement. Furthermore, the students have been tested with 6 physical fitness tests to indicate their physical performances (standing broad jump, sit and reach, 30-meter sprint, 7 level sit-up, 10-meter shuttle run, bleep test). The results of this study show that anthropometry measurement and physical performance test can be used to discriminate between students in the different type of school (NSS, SSS, NS). Besides that, this study showed that there were different performances in the physical test among students, which can help to discriminate students into the different school.